Vitamin D and Vitamin K Concentrations in Human Brain Tissue Are Influenced by Freezer Storage Time: The Memory and Aging Project - Fu, Xueyan; Shea, M Kyla; Dolnikowski, Gregory G; Patterson, William B; Dawson-Hughes, Bess; Holland, Thomas M; Schneider, Julie A; Booth, Sarah L (The Journal of nutrition, 2021)
Vitamins D and K, which are present in human brain, may have a role in neurodegenerative disease. Given the interest in measuring nutrient concentrations in archived brain samples, it is important to evaluate whether freezer storage time affects these concentrations. Therefore, we evaluated differences in vitamin D and vitamin K concentrations in human brain samples stored for various lengths of time. Postmortem brain samples were obtained from 499 participants in the Rush Memory and Aging Project (mean age 92 y, 72% female). Concentrations of vitamins D and K and their metabolites were measured in 4 regions (midtemporal cortex, midfrontal cortex, cerebellum, anterior watershed white matter) using LC-MS/MS and HPLC, respectively. The predominant forms were 25-hydroxycholecalciferol [25(OH)D3] and menaquinone-4 (MK4). ANOVA was used to determine if concentrations differed according to storage time. The geometric mean of the mean 25(OH)D3 concentration (across 4 regions) in brains stored for 1.1 to 6.0 y did not differ from that in brains stored ≤1.0 y (all P ≥ 0.37), whereas 25(OH)D3 in brains stored >6.0 y was 31-40% lower (P ≤ 0.003). MK4 had similar results, with the geometric mean MK4 concentration in the brains stored ≥9.0 y being 48-52% lower than those in brains stored ≤1.0 y (P ≤ 0.012). The 25(OH)D3 and MK4 concentrations were positively correlated across all 4 regions (all Spearman ρ ≥ 0.79, P < 0.001). 25(OH)D3 and MK4 appear to be stable in brain tissue from older adults stored at -80°C for up to 6 and 9 y, respectively, but not longer. Freezer storage time should be considered in the design and interpretation of studies using archived brain tissue.